Structure and biological activity of avian hypothalamic luteinizing hormone-releasing hormone - King, Judy A (Division of Chemical Pathology, 2018)
In 1971 Schally and co-workers (Schally et al., 1971) isolated gonadotropin-releasing hormone (now called luteinizing hormone-releasing hormone (LH-RH)) from sheep hypothalami and established that the hormone was a decapeptide with the amino acid sequence: pGlu-His-Trp-Ser-Tyr-Gly-Leu-Arg-Pro-Gly-NH₂. The peptide was subsequently synthesised (Matsuo et al., 1971b) and shown to stimulate the release of gonadotropins (luteinizing hormone and follicle-stimulating hormone) in a wide range of mammalian species (Schally et al., 1973, 1976). With the exception of amphibians, nonmammalian vertebrates have a poor gonadotropin response to synthetic mammalian LH-RH (for reviews, see Ball, 1981; Jackson, 1981; King and Millar, 1981a). Since there is considerable molecular heterogeneity in the related neurohypophysial nonapeptide hormones (oxytocin-vasopressin) amongst vertebrates (Acher et al., 1972), we postulated that differences might exist in the structure of hypothalamic LH-RH in different vertebrate classes, Utilising a combination of regionspecific antisera and chromatographic techniques, we established that amphibian hypothalamic LH-RH is identical to the mammalian peptide while avian, reptilian, and piscine hypothalamic LH-RHs differ structurally in the region Gly⁶-Leu⁷-Arg⁸ (King and Millar, 1979a, 1980), We have now conducted further studies on avian hypothalamic LH-RH, which indicate that the arginine residue in position eight of mammalian LH-RH is substituted by glutamine in this vertebrate class. Purification of LH-RH from chicken hypothalami and determination of the amino acid composition have confirmed that the structure of avian LH-RH is: pGlu-His-Trp-Ser-Tyr-Gly-Leu-Gln-Pro-Gly-NH₂.